Comparative Studies of Biosimilar Medicinal Products - O. B. Talibov (Регуляторные исследования и экспертиза лекарственных средств, 2019)
The article describes specific aspects of biosimilars research and development. The aim of the study was to analyse the ways to conduct comparative studies of biotechnological medicinal products and the main approaches to the assessment of the obtained data. The paper highlights that biotechnological products are associated with a much higher potential variability of chemical and pharmacological characteristics than small molecules. The author analyses the reasons of this phenomenon, describes mechanisms underlying the microheterogeneity of protein molecules, primarily post-translational modification. The latter has an impact on the pharmacokinetic parameters, pharmacodynamics and immunogenicity of complex protein molecules, which increases the variability of test results and makes it difficult to conduct bioequivalence studies. In addition to bioequivalence studies, biosimilars research should include comparative studies of pharmacodynamics, evaluation of therapeutic equivalence and immunogenicity. Assessment of the medicines comparability should be based on the analysis of all data provided, which requires a more flexible and sometimes individual approach on the part of regulatory authorities.